Serum Metalloproteinases 2 and 9 as Predictors of Gait Status, Pressure Ulcer and Mortality after Hip Fracture - Gumieiro, David N. [UNESP]; Rafacho, Bruna P. M. [UNESP]; Gonçalves, Andrea F. [UNESP]; Santos, Priscila P. [UNESP]; Gaiolla, Paula Schmidt Azevedo [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP]; Pereira, Gilberto José Cação [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Minicucci, Marcos Ferreira [UNESP] (Public Library of Science (PLoS), 2013)
Introduction: The aim of this study is to evaluate the serum activity of metalloproteinases (MMPs) -2 and -9 as predictors of pressure ulcer (PU), gait status and mortality 6 months after hip fracture. Methods: Eighty-seven patients over the age of 65 admitted to the orthopedic unit from January to December 2010 with hip fracture were prospectively evaluated. Upon admission, patient demographic information, including age, gender and concomitant diseases, was recorded. Blood samples were taken for analysis of MMP -2 and -9 activity by gel zymography and for biochemical examination within the first 72 hours of the patient's admission, after clinical stabilization. The fracture pattern (neck, trochanteric or subtrochanteric), time from admission to surgery, surgery duration and length of hospital stay were also recorded. Results: Two patients were excluded due to the presence of pathological fractures (related to cancer), and three patients were excluded due to the presence of PU before admission. Eighty-two patients, with a mean age of 80.4 ± 7.3 years, were included in the analysis. Among these patients, 75.6% were female, 59.8% had PU, and 13.4% died 6 months after hip fracture. All patients underwent hip fracture repair. In a univariate analysis, there were no differences in serum MMP activity between hip fracture patients with or without PU. In addition, the multiple logistic regression analysis models, which were adjusted by age, gender, length of hospital stay and C-reactive protein, showed that the pro-MMP-9 complexed with neutrophil gelatinase-associated lipocalin form (130 kDa) was associated with gait status recovery 6 months after hip fracture. Conclusions: In conclusion, serum pro-MMP-9 is a predictor of gait status recovery 6 months after hip fracture. © 2013 Gumieiro et al.
Keywords: C reactive protein; gelatinase A; gelatinase B; lipocalin; aged; blood sampling; decubitus; demography; enzyme activity; enzyme blood level; female; femur intertrochanteric fracture; femur neck fracture; femur subtrochanteric fracture; gait; hip fracture; hospitalization; human; length of stay; major clinical study; male; mortality; neutrophil; operation duration; prediction; prospective study; zymography; Acute-Phase Proteins; Aged; Aged, 80 and over; Biological Markers; C-Reactive Protein; Female; Gait; Hip Fractures; Humans; Length of Stay; Lipocalins; Male; Matrix Metalloproteinase 2; Matrix Metalloproteinase 9; Pressure Ulcer; Prognosis; Prospective Studies; Protein Binding; Proto-Oncogene Proteins; Recovery of Function; Regression Analysis; Survival Analysis; Treatment Outcome